The effect of a training program on developing the kinetic speed of the dribbling and passing skills for football junior players - J. Mahmoud, Sadiq; M. , Basim Kh. Abbas; Razzaq Waheeb Yaseen, Abdul (International Journal of Psychosocial Rehabilitation, 2020)
The study aimed at determining the effect of a training program in developing the kinetic speed of the dribbling and passing skills in football. A football player, in all playing positions during the game, needs ideal speed especially when performing the dribbling and passing skills. This is in order to reach the various competitive playing areas, as well as speeding up the rhythm of the playing. The study was based on an experimental approach whereby the researchers adopted the one-group method. The study was conducted on a sample of (24) players from the football team (Junior level) of Al-Talaba Sports Club. After the implementation of the training program, the results of the pre-tests and post-tests for the variables of the study under research (dribbling and passing) were collected. The researchers treated the results statistically using the statistical package (SPSS). The study concluded that the training program prepared by the researchers had a positive impact on the development of the kinetic speed of the dribbling skills of the study sample. The study recommended focusing on Kinetic speed training when developing training programs because of its positive impact on football players in addition to its great importance during the game. The study also recommended the departure from the traditional methods used in training.